Role of Prx1-expressing Skeletal Cells and Prx1-expression in Fracture Repair - Esposito, Alessandra (Bone, 2020)
The healing capacity of bones after fracture implies the existence of adult regenerative cells. However, information on identification and functional role of fracture-induced progenitors is still lacking. Paired-related homeobox 1 (Prx1) is expressed during skeletogenesis. We hypothesize that fracture recapitulates Prx1’s expression, and Prx1 expressing cells are critical to induce repair. To address our hypothesis, we used a combination of in vivo and in vitro approaches, short and long-term cell tracking analyses of progenies and actively expressing cells, cell ablation studies, and rodent animal models for normal and defective fracture healing. We found that fracture elicits a periosteal and endosteal response of perivascular Prx1+ cells that participate in fracture healing and showed that Prx1-expressing cells have a functional role in the repair process. While Prx1-derived cells contribute to the callus, Prx1’s expression decreases concurrently with differentiation into cartilaginous and bone cells, similarly to when Prx1+ cells are cultured in differentiating conditions. We determined that bone morphogenic protein 2 (BMP2), through C-X-C motif-ligand-12 (CXCL12) signaling, modulates the downregulation of Prx1. We demonstrated that fracture elicits an early increase in BMP2 expression, followed by a decrease in CXCL12 that in turn down-regulates Prx1, allowing cells to commit to osteochondrogenesis. In vivo and in vitro treatment with CXCR4 antagonist AMD3100 restored Prx1 expression by modulating the BMP2-CXCL12 axis. Our studies represent a shift in the current research that has primarily focused on the identification of markers for postnatal skeletal progenitors, and instead we characterized the function of a specific population (Prx1+ cells) and their expression marker (Prx1) as a crossroad in fracture repair. The identification of fracture-induced perivascular Prx1+ cells and regulation of Prx1’s expression by BMP2 and in turn by CXCL12 in the orchestration of fracture repair, highlights a pathway in which to investigate defective mechanisms and therapeutic targets for fracture non-union.